Figuras do dissenso: a subjetivação política na construção de novas memórias para a cidade de Belo Horizonte - Mariana Falcão Duarte (2017)
This study immerses in a fragment of the history of Belo Horizonte through the historical and political analysis of the Silvéria Cândida Pinto street toponym located in the neighborhood of Luxemburgo, in the south-central area of the city. The methodology employed consisted of a bibliographical review of primary and secondary sources, whose main theorizations lie in Ecléa Bosi's studies on memory and social psychology, on Walter Benjamin's history concepts, and on the concept of political subjectivation that encompasses Jacques Ranciére's ideals of democracy and identity. By making use of the urban and regional planning analytical approach combined with the ethnographic and historiographic research and analysis method, it was possible to create an urban, historical, and political panorama of the region where the street is located, from which residents' oral testimonies and vernacular photographs of the street urbanization period emerged, in addition to official documents on the origin of the street and the neighborhood made available by museums and institutions responsible for safeguarding the memory of the city. The present study did not seek to establish historical truth, but to create a scene in which the characters' functions and roles are intertwined and inverted. The space constructed from the oral testimonies analysis and the photographs form a territory of possibilities since the speech and image association allows for a clash between personal stories and official history, which, in turn, shed light in the forms of history creation and visibility, as well as in the action of hegemonic forces related to the construction of collective and official memory